READING TEACHING TECHNOLOGIES. - Boltayeva, Gulilola (Журнал иностранных языков и лингвистики, 2021)
Annotation: Teachers and schools have a lot of obligations when it comes to literacy teaching and learning. Teaching reading and writing, on the other hand, is a difficult and highly specialized vocation. Many young students enter school with little understanding of how to read and write. Teachers are responsible with assisting students in bridging the gap between their written and spoken language. Reading instruction is a dynamic and non-linear process that differs for each young pupil. Word reading and comprehension are included in the reading programs of study at key stages 1 and 2. In this article discusses about reading teaching techniques and teachnologies for from 5 to 9 classes school pupils.